PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA SEKOLAH TINGGI ILMU KESEHATAN PAYUNG NEGERI - Nursalam Uqbah Rahmat; Ningsih Suryati Dewita; Roesdy Rosnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
Employee work discipline at the STIKES Payung Negeri Pekanbaru is still not optimal, if be observed by extent Employee absences still quite high. This study aimed to determine (1) influence of leadership style, work motivation, work discipline towards employee performance and job satisfaction;(2) influence job satiscaftion toward employee performance. Population and sample in this research were the whole employee STIKes Payung Negeri Pekanbaru and the data collection methods used were interviews, questionnaire, and observation. This study uses descriptive analysis and multiple linier regression. The results showed leadership style, work motivation, work discipline have positive significant towards employee performance. The same effect of leadership style, work motivation, work discipline towards job satisfaction through employee performance. Therefore to improve employee satisfaction STIKes Payung Negeri Pekanbaru was suggested to provide capacity building trainings of leader, to provide employee motivation, to provide attention with reprimand employees reprimand employees who bad job.Keywords: Leadership Style, Work Motivation, Work Discipline, Employee Performance, Job Satisfaction